FINDINGS RELEASED FROM NAXOS, A FRENCH REAL-WORLD DATA ANALYSIS AND THE LARGEST REAL-WORLD DATA ANALYSIS ON ORAL ANTICOAGULANT EFFECTIVENESS AND SAFETY IN EUROPE AMONG PATIENTS WITH NON-VALVULAR ATRIAL FIBRILLATION - article Editorial (Евразийский Кардиологический Журнал)
Eliquis® (apixaban) was associated with a lower rate of major bleeding, stroke and systemic thromboembolic events compared to a vitamin K antagonist. Results show Eliquis was associated with a lower rate of major bleeding and comparable rates of stroke and systemic thromboembolic events versus dabigatran or rivaroxaban. This late-breaking presentation is one of 11 Bristol-Myers Squibb-Pfizer Alliance abstracts being presented at the European Society of Cardiology Congress 2019.